Presynaptic Release-Regulating mGlu1 Receptors in Central Nervous System - Pittaluga, Anna (Frontiers in Pharmacology, 2016)
Group I metabotropic glutamate (mGlu) receptors consists of mGlu1 and mGlu5 receptor subtypes. These receptors are widely distributed in the central nervous system (CNS), where they preferentially mediate facilitatory signalling in neurones and glial cells, mainly by favouring phospholipase (PLC) translocation. Based on the literature so far available, group I mGluRs are preferentially expressed at the postsynaptic side of chemical synapsis, where they participate in the progression of the chemical stimulus. Studies, however, have shown the presence of these receptors also at the presynaptic level, where they exert several functions, including the modulation of transmitter exocytosis. Presynaptic Group I mGluRs can be both autoreceptors regulating release of glutamate and heteroreceptors regulating the release of various transmitters, including GABA, dopamine, noradrenaline, and acetylcholine. While the existence of presynaptic release-regulating mGlu5 receptors is largely recognized, the possibility that mGlu1 receptors also are present at this level has been a matter of discussion for a long time. A large body of evidence published in the last decade, however, supports this notion. This review aims at revisiting the data from in vitro studies concerning the existence and the role of release-regulating mGlu1 receptors presynaptically located in nerve terminals isolated from selected regions of the CNS. The functional interaction linking mGlu5 and mGlu1 receptor subtypes at nerve terminals and their relative contributions as modulators of central transmission will also be discussed. We apologize in advance for omission in our coverage of the existing literature.